INFLUENCE OF THE ORAL HYGIENE LEVEL ON INCIDENCE RATES OF DENTAL CARIES AND GINGIVITIS IN CHILDREN AND ADOLESCENTS OF RURAL LOCALITY OF ODESSA REGION - Y.G. Chumakova; V.O. Antoshchuk (Український стоматологічний альманах)
Dental caries and inflammatory periodontal diseases predominate in the structure of oral diseases in children and adolescents.